2010
DOI: 10.1136/adc.2009.182394
|View full text |Cite
|
Sign up to set email alerts
|

Renal manifestations of Henoch-Schonlein purpura in a 6-month prospective study of 223 children

Abstract: Objective To assess the risk factors for developing Henoch-Schönlein purpura nephritis (HSN) and to determine the time period when renal involvement is unlikely after the initial disease onset. Design A prospective study of 223 paediatric patients to examine renal manifestations of Henoch-Schönlein purpura (HSP). The patient's condition was monitored with fi ve outpatient visits to the research centre and urine dipstick testing at home. Results HSN occurred in 102/223 (46%) patients, consisting of isolated hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
4
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 28 publications
(51 reference statements)
7
96
4
15
Order By: Relevance
“…While the kidneys are always involved in BD, approximately 50% of patients develop acute kidney involvement in HSP, varying from asymptomatic microscopic hematuria to severe macroscopic hematuria with proteinuria and even to nephrotic syndrome (Chang et al, 2005;Jauhola et al, 2010). Renal involvement typically occurs in the first three months after onset, more commonly with disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…While the kidneys are always involved in BD, approximately 50% of patients develop acute kidney involvement in HSP, varying from asymptomatic microscopic hematuria to severe macroscopic hematuria with proteinuria and even to nephrotic syndrome (Chang et al, 2005;Jauhola et al, 2010). Renal involvement typically occurs in the first three months after onset, more commonly with disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Purpura was designated as the necessary criterion since it was present in all children with IgAV (HSP) in the web-based pediatric vasculitis registry of PRINTO [10]. Joint involvement, which is more common in children with IgAV (HSP) than in adults [39], and renal involvement, which determines the longterm prognosis [40], were both considered as new criteria. The age criterion was deleted since it was considered to be redundant.…”
Section: Ankara 2008 Criteriamentioning
confidence: 99%
“…Persistent purpura, severe abdominal symptoms and an older age were confirmed as the most significant risk factors for later nephropathy (Bogdanovic, 2009). A prospective study showed that age over 8 years at onset (OR 2.7), abdominal pain (OR 2.1) and a recurrence of Henoch-Schönlein purpura disease (OR 3.1) were independent risk factors for developing nephritis (Jauhola et al, 2010).…”
Section: Renal Involvement In Henoch-schönlein Purpuramentioning
confidence: 99%
“…More than half also have proteinuria, which in one eighth is severe enough to cause nephrotic syndrome (Saulsbury, 2001). From a retrospective study, nephritis occurred in 46% of the Henoch-Schönlein purpura patients, consisting of isolated haematuria in 14%, isolated proteinuria in 9%, both haematuria and proteinuria in 56%, nephrotic-range proteinuria in 20% and nephrotic-nephritic syndrome in 1% (Jauhola et al, 2010). Renal involvement is in most cases mild and self-limited in children.…”
Section: Clinical Patternsmentioning
confidence: 99%
See 1 more Smart Citation